2015
DOI: 10.1159/000381663
|View full text |Cite
|
Sign up to set email alerts
|

High Peritoneal Glucose Exposure Is Associated with Increased Incidence of Relapsing and Recurrent Bacterial Peritonitis in Patients Undergoing Peritoneal Dialysis

Abstract: Aim: We investigated the association of peritoneal glucose exposure and dialysis exchange number with peritonitis outcome in patients undergoing continuous ambulatory peritoneal dialysis (CAPD). Methods: The first episodes of bacterial peritonitis were retrospectively analyzed in 187 CAPD patients. Peritoneal glucose exposure was calculated based on PD prescription at the onset of peritonitis. Results: Patients with peritoneal glucose exposure ≤140 g/day showed a higher and complete cure rate of peritonitis (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
1
6
0
1
Order By: Relevance
“…These results are in keeping with those of a recently published retrospective observational study of 230 PD patients who had experienced peritonitis-free survival for at least 1 year at a single Dutch center between 1990 and 2010 (19,20). This investigation observed a higher crude risk of peritonitis in PD patients with high dialysate glucose exposure (> 44 mmol/L/ day) in the first year compared with those who had a low dialysate glucose exposure (≤ 44 mmol/L/day) (HR 0.71, 95% CI 0.51 -0.99).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results are in keeping with those of a recently published retrospective observational study of 230 PD patients who had experienced peritonitis-free survival for at least 1 year at a single Dutch center between 1990 and 2010 (19,20). This investigation observed a higher crude risk of peritonitis in PD patients with high dialysate glucose exposure (> 44 mmol/L/ day) in the first year compared with those who had a low dialysate glucose exposure (≤ 44 mmol/L/day) (HR 0.71, 95% CI 0.51 -0.99).…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, a previous retrospective, single-center study of 187 CAPD patients experiencing a first episode of peritonitis between 2009 and 2013 found an association between higher glucose exposure of > 140 g/day and a lower complete cure rate of peritonitis on univariate analysis (51.7% vs 66 %, p = 0.047) (20). In addition, the authors also found that the high glucose exposure group experienced more frequent occurrences of relapsing or recurrent peritonitis (21.8% vs 10%, p = 0.026) and catheter removal (26.4% vs 14%, p = 0.033).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…21 High glucose exposure on PD has been shown to be a predictor for peritonitis in other observational studies. 22,23 Another explanation for delaying peritonitis may be due to the presence of a higher initial RKF in those treated with incremental PD. Several studies have demonstrated low RKF as an independent risk factor for peritonitis, manifesting as higher peritonitis rates and shorter peritonitis-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo y a pesar de haber disminuido marcadamente las complicaciones, la peritonitis representa la principal complicación aguda de la diálisis peritoneal, causando hospitalización, pérdida del catéter, abandono de la técnica y trasferencia a hemodiálisis, así como mortalidad [7][8][9][10][11][12] , la etiología bacteriológica es diversa [13][14][15][16][17][18][19][20][21][22][23] , su diagnóstico, tratamiento y pronóstico están, por lo general, claramente definidos 24-28 y su pronóstico es variable [29][30][31][32][33] .…”
Section: Introductionunclassified